Gluten-free made simple : easy everyday meals that everyone can enjoy - Dahlstrom, Carol Field (St. Martin's Griffin, 2011)
"Most families with a member with Celiac disease struggle to get food on the table that everyone can enjoy. This easy-to-use cookbook focuses on creating simple and tasty recipes with a minimum of stress. Most of the dishes use ingredients that are easily found in supermarkets and don't require the exotic flours or expensive ingredients found in other gluten-free cookbooks. With over 100 gluten-free recipes for every meal of the day from entrees, soups, salads, and appetizers, to desserts and other baked goods, here is a book that lives up to the promise of making it so simple even first time cooks can create gluten-free meals the whole family can share. Gluten-Free Made Simple also includes: Complete nutritional analysis for every recipe, step-by-step photos helpful to beginners, a list of naturally gluten-free foods available in supermarkets, icons to indicate high protein, low fat, high fiber, casein-free, egg-free and/or vegetarian, information about gluten, celiac disease and living a gluten-free lifestyle. One of the fastest growing segments in nutrition is understanding the role of gluten and its effect on the immune system. This book offers guidance to people struggling to make sense of their food options while cooking delicious food for themselves and their families"--